2018
DOI: 10.1208/s12249-017-0941-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Population Bioequivalence (PBE) Statistical Test Using an IPAC-RS Database of Delivered Dose from Metered Dose Inhalers

Abstract: This article reports performance characteristics of the population bioequivalence (PBE) statistical test recommended by the US Food and Drug Administration (FDA) for orally inhaled products. A PBE Working Group of the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) assembled and considered a database comprising delivered dose measurements from 856 individual batches across 20 metered dose inhaler products submitted by industry. A review of the industry dataset identified var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…, the type I error or false positive rate, FPR) in the presence of between-batch variations. In addition, Morgan et al ( 9 ) confirmed the increase of at least 15% of the probability to incorrectly conclude on equivalence (type I error) when neglecting between-batch variability in PBE studies. This same study also highlights an increase of the probability to incorrectly reject equivalence ( i.e.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…, the type I error or false positive rate, FPR) in the presence of between-batch variations. In addition, Morgan et al ( 9 ) confirmed the increase of at least 15% of the probability to incorrectly conclude on equivalence (type I error) when neglecting between-batch variability in PBE studies. This same study also highlights an increase of the probability to incorrectly reject equivalence ( i.e.…”
Section: Introductionmentioning
confidence: 96%
“…In vitro bioequivalence testing is not considered and evaluated in the same way by all instances taking part in the process ( 7 , 8 ). Indeed, in the USA, FDA recommends the use of population bioequivalence (PBE) ( 9 , 10 ), whereas Europe recommends using average bioequivalence (ABE) ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations